Implementation of Hand Washing Dance Method to Knowledge of Hand Washing Techniques of Preschool Age Children During the Covid 19 Pandemic - Hastin Ika Indriyastuti; Juni Sofiana; Kusumastuti Kusumastuti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Positive habits need to be instilled from an early age, so that children get used to it, including the habit of washing hands with soap. Instilling hand washing techniques in children must be carried out with something unique, for example by playing, so that children feel happy. Hands Washing Dance is packaged expressively according to the character of PAUD (Early Childhood Education) students who prioritize learning while playing, which is expected to foster a sense of enthusiasm for children in washing hands after activities. The purpose of this community service is to provide care for preschool-aged children so that they can practice good hand washing techniques with the handwashing dance method during the Covid-19 Pandemic Period”. The method used is an observation method. Results: from the results of the pretest, 60% of respondents got bad criteria, and 40% of other respondents got very bad criteria. After applying the Hand Washing Dance and doing the post test the results were 10% of respondents with sufficient results, and 90% of respondents with good results. Conclusion: The ability of the respondent to wash hands after using the Handwashing dance method increased.